1999
DOI: 10.1038/sj.onc.1202755
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen induces p21WAF1 and p27KIP1 expression in estrogen receptor-negative lung cancer cells

Abstract: Tamoxifen (Tam), besides its action as an anti-estrogen, also inhibits cell proliferation of estrogen receptor (ER)-negative cancer cells by an unknown mechanism. In this study, we used ER-negative lung cancer cells to clarify such ER-independent inhibitory eect of Tam. We found that Tam induced G1 growth arrest in these cells. However, our results indicated that the expression of G1 cyclins (including D1, 2, 3 and E) was not regulated by Tam in these lung cancer cells. Additionally, the protein levels of G1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 46 publications
1
14
1
1
Order By: Relevance
“…KIP1 in an ER-independent manner (Lee et al, 1999). In this study, we show that Tam activates p21 WAF1 expression through Sp1-binding site located between bp 783 and 774 in the p21 WAF1 promoter.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…KIP1 in an ER-independent manner (Lee et al, 1999). In this study, we show that Tam activates p21 WAF1 expression through Sp1-binding site located between bp 783 and 774 in the p21 WAF1 promoter.…”
Section: Discussionmentioning
confidence: 74%
“…KIP1 (Lee et al, 1999). We found that upregulation of CDKIs in lung cancer cells by Tam led to reduced activity of cyclin E-associated kinases, accumulation of hypophosphorylated retinoblastoma (Rb) protein and G1 growth arrest in these cells.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Suppression of tumor growth by 4OH-Tam has been associated with downmodulation of cyclin D1 (Jang et al, 2001). 4OH-Tam induces the expression of p21 Waf1 and p27 Kip1 , which block the activating effect of cyclin D1 (Lee et al, 1999b). In this report, we have tested the ability of 4-HPR and 4OH-Tam to inhibit the growth of rhabdoid cells in vitro and tumors in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…WAF1 and p27 KIP1 , combined with a reduction in cyclin D1 protein that acts to inhibit cyclin D/CDK4 and cyclin E/CDK2 activity and arrest cell cycle progression (Wilcken et al 1997, Lee et al 1999, DoisneauSixou et al 2003. Interestingly, over-expression of cyclin D1 (Wilcken et al 1997) or cyclin E can alleviate tamoxifen inhibition of MCF-7 cells in culture (Dhillon & Mudryj 2002).…”
Section: Introductionmentioning
confidence: 99%